An empirical study of educational robotics as tools for group metacognition and collaborative knowledge construction - Socratous, Chrysanthos; Ioannou, Andri (My University, 2019)
The affordances of Educational Robotics (ER) for advancing teaching and learning has become a widely researched topic. This study aims to identify the major components of collaborative knowledge construction in an ER learning environment and to investigate the mediating role of ER as mindtools to support group metacognition. Data analysis involved a micro-level examination of students’ discourse, interaction with the technology, peers and the facilitator, using fine-grained analysis of video and audio recordings. The results made evident that metacognition, along with questioning and answering, were prevalent elements of collaborative knowledge construction around ER. We support that ER can be used as a learning tool and can be effective in supporting group metacognition through immediate feedback, openly accessible programmability and students’ embodied interaction with the physical robot. Beyond the instrumental role of ER for supporting metacognitive processes in CSCL settings, the study provides initial evidence for a temporal relation of metacognitive talk to collaborative talk in group problem-solving.
Keywords: Cognitive systems; Computer aided instruction; Educational robots; Knowledge management; Robotics; Students